Simultaneous Fluorescein Angiography and Spectral Domain Optical Coherence Tomography Correlate Retinal Thickness Changes to Vascular Abnormalities in an In Vivo Mouse Model of Retinopathy of Prematurity - Olachi J. Mezu-Ndubuisi; Lauren K. Taylor; Jamee A. Schoephoerster (Journal of Ophthalmology)
Background. Retinopathy of prematurity (ROP) is a condition of abnormal retinal vascular development (RVD) in premature infants. Fluorescein angiography (FA) has depicted phases (early, mid, late, and mature) of RVD in oxygen-induced retinopathy (OIR) mice. We sought to establish the relationship between retinal structural and vascular changes using simultaneous FA and spectral domain optical coherence tomography (SD-OCT). Method. 63 mice were exposed to 77% oxygen at postnatal day 7 (P7) for 5 days, while 63 mice remained in room air (RA). Total retinal thickness (TRT), inner retinal thickness (IRT), and outer retinal thickness (ORT) were calculated at early (P19), mid (P24), late (P32), and mature (P47) phases of RVD. Results. TRT was reduced in OIR (162.66 ± 17.75 μm, n=13) compared to RA mice at P19 (197.57 ± 3.49 μm, n=14), P24, P32, and P49 (P<0.0001). ORT was similar in RA and OIR mice at all ages (P>0.05). IRT was reduced in OIR (71.60 ± 17.14 μm) compared to RA (103.07 ± 3.47 μm) mice at P19 and all ages (P<0.0001). Conclusion. We have shown the spatial and temporal relationship between retinal structure and vascular development in OIR. Significant inner retinal thinning in OIR mice persisted despite revascularization of the capillary network; further studies will elucidate its functional implications in ROP.